Socialization of The Regional General Election Commission to Beginning Voters in Regional Head Elections of Sumedang Regency: Socialization of The Regional General Election Commission to Beginning Voters in Regional Head Elections of Sumedang Regency - Yuningsih, Siti Hadiaty (Communication in Research and Publications (CRP), 2023)
in this research is useful to provide broader information about how the effectiveness of elections in providing political understanding in order to increase public political awareness The General Election Commission consistently strives to increase community participation, especially Sumedang Regency for the prevention of golput. That activities carried out by the General Election Commission and the Head of Cimanggung Regency socialized the election to the people who were present, explained in detail the importance of elections in people's lives after that also made a video which was uploaded to YouTube related to the socialization of the election.